The Analysis of the Implementation of Good Financial Governance in Public Sector Financial Management in Timor Leste - Maia, Fonseca de Jesus; Ximenes, Elias; Boquifai, Petronela M.; Ratnawati, Tri (Sean Institute, 2025)
This study analyzes the implementation of Good Financial Governance (GFG) in public sector financial management in Timor Leste, focusing on transparency, accountability, and public participation. Using a qualitative-descriptive approach and case study method, data were collected through document analysis and literature review from international institutions such as the IMF, World Bank, and PEFA. The findings reveal partial progress, notably through the adoption of the Integrated Financial Management Information System (IFMIS), which has improved transparency. However, challenges remain in enforcing audit recommendations, institutionalizing citizen participation, and aligning national policies with local implementation. Comparative case studies from Cambodia, Jamaica, and Scotland highlight the importance of institutional reform, leadership, and legal enforcement. The study recommends enhancing fiscal literacy, strengthening oversight capacity, and establishing participatory budgeting mechanisms. Overall, the research underscores that effective GFG is essential for sustainable development, requiring both technical innovations and structural reforms to ensure inclusive, transparent, and accountable financial governance.